STRATEGI PEMASARAN PADA USAHA SARANG BURUNG WALET DI KECAMATAN TANGGETADA KABUPATEN KOLAKA, SULAWESI TENGGARA - Prihantini, Campina Illa; Haerul, Haerul; Syahrir, Syahrir; Masitah, Masitah (Universitas Galuh, 2023)
Swallow's Nest business is one of the businesses that have bright prospects to be developed in Indonesia at this time. This is supported by the appropriate environmental and geographical conditions and resources available to support the life of swallows that can be found in several regions in Indonesia. This study analyzes the marketing strategy of the swallow business as one of the promising businesses in the future. The analysis was carried out by qualitative descriptive analysis method, namely SWOT analysis. The results of the analysis showed that the strategy is in Quadrant I, namely intensive strategy and integrative strategy. Recommendations swallow's nest marketing strategy produces 4 main strategies that hope, can be the basis and consideration in the development of Swallow's Nest business that is able to encourage people's independence in economic life.